Application of Domestication and Foreignization Strategies in Subtitle Translation – A Case Study of The Legend of Miyue - Li, You (Pacific International Journal, 2025)
This study analyzes the application of domestication and foreignization strategies in the English subtitle translation of the Chinese historical drama The Legend of Miyue. The research aims to evaluate how these strategies impact cultural transmission and subtitle quality, and to propose a more systematic framework for strategy selection. Through textual analysis of the subtitles, the study examines how specific cultural elements are translated. The findings reveal a dynamic interplay between domestication, which enhances comprehensibility for the target audience, and foreignization, which preserves the cultural authenticity of the source text. A key contribution of this study is the proposal of a strategy-selection model based on the cultural load and informational function of the content. This model provides a practical tool for translators to make informed decisions, balancing readability with cultural fidelity. The study concludes that a flexible, context-sensitive application of both strategies is essential for effective cross-cultural communication through audiovisual translation, offering significant implications for both translation practice and the global dissemination of culturally rich media.